Focal laser application versus bevacizumab for treatment of central serous chorioretinopathy - Ali A Ghali (Wolters Kluwer Medknow Publications, 2019)
Aim To report and compare the efficacy of macular grid laser versus intravitreal bevacizumab injection (IVBI) in patients with central serous chorioretinopathy (CSCR). Patients and methods A prospective study on 36 eyes of 35 patients with CSCR was conducted. The diagnosis of CSCR was established by fluorescein angiography and optical coherence tomography (OCT). All patients underwent measurement of best-corrected visual acuity, intraocular pressure, dilated fundus examination, and (OCT) imaging at baseline and follow-up visits. Fluorescein angiography was performed at baseline visit and thereafter depending on clinical and OCT findings. Patients were classified into group A, comprising 19 patients who were treated with macular grid laser and group B, comprising 17 patients who were treated with IVBI. The outcome measures were the resolution of neurosensory detachment, improvement in visual acuity, and resolution of leakage. All cases were evaluated after 3, 6, 12, and 24 weeks. Data were classified into two groups and statistically analyzed. Results In group A, the mean age of patients was 43.6 years (range, 23-52 years), there were 11 (57.89%) males and eight (42.10%) females, and the mean of follow-up period was 9.2 months (range, 7-18 months). The mean log MAR visual acuity score improved from 0.8 to 0.40 after 3 months of follow-up. The mean baseline central macular thickness (CMT) was 466 µm (range, 358-576 µm), which decreased to 309 µm (range, 268-356 µm) after 6 weeks, with statistically significance difference change from the baseline, and to 247 µm (range, 225-319 µm) after 3 months, with statistically significance difference change from the baseline (P<0.001). In group B, the mean age of patients was 39.7 years (range, 42-57 years), there were nine (52.94%) males and eight (47.05%) females, and the mean follow-up period was 9.1 months (range, 6-16 months). The mean log MAR visual acuity improved from 1.00 to 0.40 after 3 months of follow-up. The mean baseline CMT was 454 µm (range, 334-567 µm), which decreased to 312 µm (range, 264-359 µm) after 6 weeks, with statistically significant difference change from baseline, and to 252 µm (range, 232-338 µm) after 3 months, with statistically significant difference change from the baseline (P<0.001). After 3 months of follow-up time, there was no significant difference in mean CMT between booth groups (247 vs. 252 µm). The mean baseline visual acuity improved in both groups, without significant difference between them. No serious adverse effects have been observed in both groups. Conclusion Both macular grid laser and IVBI for CSCR can lead to improvements of visual acuity and hasten recovery period. Macular grid laser may be considered as effective as anti-vascular endothelial growth factor for treatment of CSCR. More studies using larger scales may be needed to clarify the uncertain relationship between pathogenesis and results of treatment.